Analysis of effect Magnesium Ammonium Phospate (MAP) Concentration on Struvite Morphology in A Vertical Reactor - Luluk Edahwati; Sutiyono; Atika Andini; Wahyu Dwi Lestari; Tria Puspa Sari; Ndaru Adyono; Novel Karaman (BIOMEJ, 2021)
Struvite was a white crystal known as Magnesium Ammonium Phosphate Hexahydrate (MgNH4PO4.6H2O). In industry, struvite was found in the pipes crust which the hot fluid through passes. Struvite is often used as fertilizer because it contains phosphate content. The one of benefits of struvite crystals is slow release fertilizer, so it can be more durable, which is good for the growth of the plants. The Precipitation technology is currently one of the most widely applied technologies in struvite formation. The process of forming struvite is carried out by using a vertical reactor. The process started by mixing the equimolar solutions of MgCl2, NH4OH, and H3PO4 with a concentration ratio of 1: 1: 1 and 1: 1: 2. Theprocess was carried out with the condition at the 30°C while the air inlet rate was 1.25 liters/min. The pH of the solution is pH 9 and controlled using NaOH solution. The process was carried out in the steady state condition. Then the solution was filtered and solid was dried at room temperature for 48 hours. From this study, the concentration ratio of 1:1:2 was obtained the best of struvite compared to the others ratio. The solid was analyzed by using the SEM-EDX instrument. The morphology of struvite was formed an irregular pyramid like crystal or commonly referred to as an authorhombic shape.